Life through my eyes from Kampung Kenang to Kasoa - Muhamad Hafiz Ismail 1986- (MPH Group Publishing Sdn. Bhd, 2014)
After several years of teaching at Sekolah Kebangsaan Kampung Kenang in Perak, Muhamad Hafiz bin Ismail, Author of Life Through My Eyes: A Teacher's Little Steps Towards Perfection, left to pursue a Master's degree in International Development and Education at Newcastle University in the UK. As part of his studies, he ventured into the West African country of Ghana with a group of fellow students, to study the reflective practices of teachers in the country. Specifically, the several schools run by Omega Schools, a social enterprise that aims to provide quality education at the lowest possible cost to the poor, located in the Ghanaian city of Kasoa. A continuation of his blogged-about adventures in teaching and education, Life Through My Eyes 2: From Kampung Kenang to Kasoa mostly chronicles his time in Ghana and compares his experiences in Malaysia and the UK, with some personal musings in between. Hafiz has chosen to immerse himself in a world where, despite poverty and the lack of what many of us take for granted, people still put a premium on education. In the end, he comes away with new perspectives of his chosen field and the realisation that he still has more to learn and do as an educator.